J. B. Clark's Formulae of Wages and Interest - Padan, R. S. (Journal of Political Economy, 1901)
THE recent volunme by Professor J. B. Clark on Tue Distributiol of kVealtli is an important contribution to the literature bearing on the interest question. The author, in no uncertain manner, takes sides with those who find the explanation of interest in the productive character of capital. " Tue power of capital to create the prodzuct is, tle,,, thie basis of interest."' What may be called the instinctive or intuitive view of mankind is in line with tlis doctrine; since the inducement to create capital in the beginning was its productive efficiency. This samne productive efficiency has been the only economic inducement o employ capital. Indeed, the surplus product due to capital is the only economic justification of the existence of capital; and surely the basis of the remuneration of capital must lie in the circumstances that afford its justification. But Professor Clark has not been content to find merely the basis of interest in productivity. He has industriously sought to establish a formula that will quantitatively identify the rate of interest with the